2023
DOI: 10.1038/s41598-023-30882-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Internet use patterns among older adults in England from before to after the outbreak of the COVID-19 pandemic

Abstract: The COVID-19 pandemic brought about an increased reliance on the Internet for various daily activities. Given the known digital divide, it is important to understand whether older adults changed their Internet use patterns, but current evidence is limited to cross-sectional studies. This study documents changes in frequency and types of Internet use among older adults from before to shortly after the outbreak of the COVID-19 pandemic (2018/2019 to June/July 2020), and the factors predicting regular use during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Unlike previous research showing younger people are more likely to seek health information online, this distinction is less pronounced in our study 38 . One contributing factor is the past 3-years COVID-19 pandemic changing how people access health information, with prolonged lockdowns driving older adults online too 39 . The fix effect model in our study has the similar conclusion that over the COVID-19 pandemic, people have In this study, we carefully analyze how PD-related information propagates and what kind of PD-related posts gain popularity within the social network.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous research showing younger people are more likely to seek health information online, this distinction is less pronounced in our study 38 . One contributing factor is the past 3-years COVID-19 pandemic changing how people access health information, with prolonged lockdowns driving older adults online too 39 . The fix effect model in our study has the similar conclusion that over the COVID-19 pandemic, people have In this study, we carefully analyze how PD-related information propagates and what kind of PD-related posts gain popularity within the social network.…”
Section: Discussionmentioning
confidence: 99%
“…Among British people, 53% admitted they would not have coped through the pandemic without digital technology, underlying the urgency and necessity for digital engagement during the pandemic, which might also explain the relatively quick transition we observed in this study. However, other societal groups with traditionally low digital engagement, such as older adults, did not show a significant increase in use of the Internet over the course of the COVID-19 pandemic in England [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that middle-aged and older adults use the Internet to satisfy their informational, psychological, social, and entertainment needs (Choi and DiNitto, 2013a; Wong et al ., 2014; Schehl et al ., 2019; Yoon et al ., 2020). Studies have also revealed diverse patterns of Internet usage among older adults, such as the underlying causes of continued or discontinued usage, frequency and type of usage in different groups, and their engagement with the Internet (Choi and DiNitto, 2013b; Szabo et al ., 2019; Wallinheimo and Evans, 2022; Kung and Steptoe, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%